2019
DOI: 10.3390/mi10120821
|View full text |Cite
|
Sign up to set email alerts
|

Surface/Interface Engineering for Constructing Advanced Nanostructured Light-Emitting Diodes with Improved Performance: A Brief Review

Abstract: With the rise of nanoscience and nanotechnologies, especially the continuous deepening of research on low-dimensional materials and structures, various kinds of light-emitting devices based on nanometer-structured materials are gradually becoming the natural candidates for the next generation of advanced optoelectronic devices with improved performance through engineering their interface/surface properties. As dimensions of light-emitting devices are scaled down to the nanoscale, the plentitude of their surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Much research on semiconductor surfaces caused by cleaving in ultrahigh vacuum suggested that the formation of surface states is attributed to dangling bonds at the surface [49]. According to a previous report [47], the schematic diagram of the surface level is shown in Figure 1. The surface states could also be divided into donor states or acceptor states based on the behavior of the electrons.…”
Section: Surface and Interface Statesmentioning
confidence: 93%
See 1 more Smart Citation
“…Much research on semiconductor surfaces caused by cleaving in ultrahigh vacuum suggested that the formation of surface states is attributed to dangling bonds at the surface [49]. According to a previous report [47], the schematic diagram of the surface level is shown in Figure 1. The surface states could also be divided into donor states or acceptor states based on the behavior of the electrons.…”
Section: Surface and Interface Statesmentioning
confidence: 93%
“…A surface could be defined as atomic layers that do not have three-dimensional continuous environment of bulk materials, three-dimensional continuous environment, or the periodicity of the infinite lattice that is destroyed by the existence of nanostructured surface. For crystal structures, in the direction of the vertical surface, the potential energy of lattice atoms could not have corresponding symmetry, and some new eigenvalues could be obtained in the Hamiltonian characteristic value when the Schrodinger equation is applied through the theory of quantum mechanics [47]. A new energy level could appear and be defined as a surface state, as shown in Figure 1.…”
Section: Surface and Interface Statesmentioning
confidence: 99%
“…[265] Suffering from the defects and surface states, which usually lead to the non-radiative recombination in 1D atomic crystals, the device only shows a broad sub-bandgap electroluminescence (EL) emission centered at 380 nm. To minimize the influence of surface/interface states and improve efficiencies, stabilities, and lifetime of devices, various strategies have been explored, including shell layer shielding [266], interfacial structure optimization [267][268][269], surface functionalization [270], etc. You et al reported a feasible method of directly bonding active n-ZnO nanowires array onto AlN-coated p-GaN wafer [271].…”
Section: D-f)mentioning
confidence: 99%
“…Study on β-Ga 2 O 3 and its function as the substrate for vertical structure LEDs have been intensively investigated. Some of the key advantages of β-Ga 2 O 3 are high n-type conductivity, low lattice mismatch with III-nitrides, and high transparency (>80%) in blue and UV region, enabling β-Ga 2 O 3 as a highly potential substrates for high-performance light-emitters.In another review paper, Zhou et al [2] summarized recent studies on the interface/surface properties of low-dimensional materials and structures. Importantly, the performance of nanostructured LEDs can be significantly improved by engineering their surface/interface characteristics with a focus on the surface/interface purification, quantum dots-emitting layer, surface ligands, and optimization of device architecture.The recent progress made in AlGaN nanowires for UV LEDs is reported in the third review paper, entitled "AlGaN nanowires for UV LEDs: Recent progress, challenges, and prospects" [3].…”
mentioning
confidence: 99%
“…In another review paper, Zhou et al [2] summarized recent studies on the interface/surface properties of low-dimensional materials and structures. Importantly, the performance of nanostructured LEDs can be significantly improved by engineering their surface/interface characteristics with a focus on the surface/interface purification, quantum dots-emitting layer, surface ligands, and optimization of device architecture.…”
mentioning
confidence: 99%